Music vs noise: a comparison of loudness estimates - MIŚKIEWICZ, A.; RAKOWSKI, A. (Archives of Acoustics, 1992)
The aim of this study was to examine whether loudness estimates of music are performed according to the same principles as loudness judgements of non-musical sounds. For this purpose loudness estimates of short musical passages were compared with those of noise signals. Spectral energy distribution of noise was matched to that of music. The results show that loudness judgements of music and noise agree reasonably well. This finding suggests that loudness of musical tones may also be determined by means of objective methods for loudness calculation, which are employed in measurements of non-musical sounds.